Verb Formation Errors in Structuring Simple Past Sentences - Anum Dahlia; Harnani (Universitas Widyatama, 2022)
This study is an investigation of college students’ English tense knowledge, according to their work of writing simple past sentences. The students’ written work was analyzed to find the most frequent errors made by students when they were writing their activities done in the day before. The errors were then identified in the sentences on their writing. The study used descriptive qualitative method, and was conducted through (a) identifying the most frequent errors in student’s simple past sentences, (b) classifying the errors into their categories, and (c) analyzing what causes the errors to be made. The result shows that the most frequent errors made by college students in writing simple past sentences are errors of verb formation. The verb formation errors are classified into three forms of error: regularizations, archi-forms and alternating forms. The dominant errors found in this research are archi-form (88%) and alternating form (12%). The errors are most likely caused by the students’ confusion in selecting a class member of verb as there are two choices to use, the students’ growth of grammar knowledge that make them have bigger or more selection of verb use and the students’ comprehension failure of mastering tense.